(untitled) (Modern education and development, 2025)
This article explores effective methods and approaches in learning the German language. It discusses the significance of language immersion, grammar-translation techniques, communicative practices, and the integration of digital tools. The paper aims to highlight how these strategies can enhance language acquisition, promote motivation, and develop all four language skills: reading, writing, listening, and speaking.